Quando la vita prevale sull'opera. Spunti critici a margine di due letture. (ENTHYMEMA, 2010)
Reading two recently published works – Jay Parini’s The Last station and Pavel Basinsky’s Begstvoiz raja [Escape from heaven] – is the starting point of a reflection, in which we notice how, today, the attention of tolstovedy and the researchers in general is largely focused on the figure of Tolstoy man/thinker and only rarely on Tolstoy writer. A quick overview of the main speeches at various international conferences and study days, 100 years after the death of the writer, highlights the favourite subject of today's researches: the context, the biographical notes often overcome on the text, which really 100 years ago was able to offer so much to the young formalist experimentations. Today the memorialist or the press of the time echo are used to propose to the reader the family gossip. The archive work of many scholars and writers, who have spent years leafing through newspapers and old diaries, is commendable; but are we sure that everything has already been said about the style and the thematic of the works themselves? I don't think so; the lack of real and full bodied works, that only great scholars know how to produce (and the Slavic fortunately still boast big talents) is felt and we should somehow begin to compensate this deficiency.